P103 Culture and culture independant identification of bacterial communities in the cystic fibrosis respiratory tract. (14th November 2013) - Einarsson, GG; McCaughan, J; Fodor, AA; Wolfgang, MC; Tunney, MM; Elborn, JS
Abstract : Introduction and Aims: The identification of complex chronic polymicrobial infections, such as those observed in the cystic fibrosis (CF) airways, are often a diagnostic challenge. Few studies have compared culture-dependent methods with molecular identification making it hard to describe bacterial communities in a comprehensive manner. The aim of the study is to compare four different methods with respect to their similarities and differences in detection of bacteria. Methods: We compared41 sputum samples fromroutine clinical-culture, extended-culture (aerobic and anaerobic), and molecular identification such as Roche 454-FLX Titanium and T-RFLP to assess concurrence between methodologies in detecting bacteria. The agreement between methodologies in detecting either absence or presence of bacterial taxa was assessed by Kappa (κ) statistics. Results: The majority of bacterial taxa identified by culture were also identified with molecular analysis. In total 2, 60, 25, and 179 different bacterial taxa were identified with clinical-culture, extended-culture, T-RFLP and 454-FLX respectively. Clinical-culture, extended-culture and T-RFLP were poor predictors of species richness when compared to 454-FLX (p < 0.0001). Agreement between methods for detecting Pseudomonas sp. and Burkholderia sp. was good with κ ≥ 0.7 [p < 0.0001] and κ ≥ 0.9 [p < 0.0001] respectively. Detection of anaerobic bacteria, such as Prevotella sp. and Veillonella sp., was moderate between extended-culture and 454-FLX with κ = 0.461 [p < 0.0001] and κ = 0.311 [p = 0.032] respectively, and good between T-RFLP and 454-FLX with κ = 0.577 [p < 0.0001] and κ = 0.808 [p < 0.0001] respectively. Agreement between methods for other main bacterial taxa, such as Staphylcoccus sp. and Streptococcus sp., was poor with only a moderate agreement for detection of Streptococcus sp. observed between T-RFLP and 454-FLX (κ = 0.221 [p = 0.024]). Conclusions: This study demonstrates the increased sensitivity culture-independent microbial identification such as the 454-FLX have over clinical-culture, extended-culture and T-RFLP methodologies. The extended-culture detected majority of the most prevalent bacterial taxa associated with chronic colonisation of the CF airways which were also detected by culture-independent methodologies. However, agreement between methods in detecting number of potentially relevant bacteria is largely lacking.